GSTM1 genotype is an independent prognostic factor in clear cell renal cell carcinoma - Coric, Vesna M.; Simic, Tatjana P.; Pekmezovic, Tatjana D.; Basta-Jovanovic, Gordana M.; Savic-Radojevic, Ana R.; Radojevic-Skodric, Sanja M.; Matic, Marija G.; Suvakov, Sonja R.; Dragicevic, Dejan P.; Radic, Tanja M.; Dzamic, Zoran M.; Pljesa-Ercegovac, Marija S. (Urologic oncology, 2017)
Owing to dual functionality of cytosolic glutathione S-transferases (GSTs), they might affect both the development and the progression of renal cell carcinoma (RCC). However, the data on the prognostic value of GST polymorphism in patients with RCC are scarce. Hence, we evaluated the effect of GST gene variants on both the risk of RCC development and the postoperative prognosis in patients with clear cell RCC (ccRCC). GST genotypes were determined in 305 patients with RCC and 326 matched controls, whereas the overall survival was evaluated in patients with ccRCC only. The presence of GSTM1:ASK1 protein-protein interaction in ccRCC tissue samples was analyzed by methods of immunoprecipitation and immunoblot. We noted an increased risk of RCC development in carriers of GSTM1-null and GSTP1-variant genotype (P<0.05). On the contrary, survival analysis indicated shorter overall survival for patients with ccRCC with GSTM1-active genotype (P = 0.026). Furthermore, patients with ccRCC with GSTM1-active genotype had significantly higher hazard ratio (P<0.05), in analyzed regression models, compared with the carriers of GSTM1-null genotype. Finally, the presence of GSTM1:ASK1 protein-protein interaction was found in all RCC tissue samples studied. Carriers of GSTM1-null and GSTP1-variant genotypes are in increased risk of RCC development. On the contrary, GSTM1-null genotype is associated with favorable postoperative prognosis in ccRCC. The possible molecular mechanism underlying the role of GSTM1 protein in RCC progression might be the presence of GSTM1:ASK1 protein-protein interaction. Hence, determination of GSTM1-genotype might serve as a valuable indicator in both RCC risk assessment and postoperative prognosis. •Patients with clear cell RCC and GSTM1-null genotype have longer overall survival.•GSTM1-active genotype is an independent predictor of higher ccRCC mortality risk.•ASK1:GSTM1 interaction might be mechanism underlying GSTs’ prognostic role in ccRCC.